Optimization of solid phase microextraction conditions for determination of triazines - Hadoudi Nouhaila; Mourabit Fouad; Assouik Saida; Amhamdi Hassan; Ahari M’hamed (E3S Web of Conferences, 2023)
A simple, solvent-free, and field-compatible approach to sample preparation is provided by the basic process known as solid-phase micro extraction (SPME). The aim of this study was to improve the circumstances under which triazines were extracted from aqueous matrices. The complex technique enabled the detection of the analytes in the water at a physiological level. An evaluation of the practicability of the most commercially available fiber coatings has been conducted. The porous materials (Carbowax/DVB and PDMS/DVB) extracted more efficiently than homogeneous ones (PDMS and polyacrylate). Further investigation has been focused on 65 mm PDMS/DVB fiber. Solid phase microextraction is a technique based on the partition equilibrium of analytes between the sample and the fiber. Therefore, 60 minutes were required to reach equilibrium at room temperature. The desorption efficiency at 3 temperature levels had been compared and 270 °C was retained. Experiments were performed with a Finnigan MAT GCQ Model installed with a 30-m x 0.32-mm ID, ZB-5 (0.25-mm film thickness) fused-silica capillary column, and Helium as a carrier gas (at 30 kPa), The ion trap mass spectrometer was operated in the electron ionization (EI) mode. Keywords: Fiber coating, Gaz chromatography, Mass spectrometry, Pesticides, Water matrices, Analysis.